2019
DOI: 10.3390/polym11081359
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Thermal Conductivity of Epoxy Resin Impregnated Nano-h-BN Modified Insulating Paper

Abstract: Epoxy resin-impregnated insulation paper (RIP) composites are used as the inner insulation of dry condenser bushing in the ultra-high voltage direct current (UHVDC) power transmission system. To improve the dielectric properties and heat conductivity of RIP, hexagonal boron nitride (h-BN) nano-flakes are added to the insulation paper at concentrations of 0–50 wt % before impregnation with pure epoxy resin. X-ray diffraction (XRD), scanning electron microscopy (SEM) observations, thermal conductivity as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…[37] Mi et al [38] used the plasma technique to increase hydroxylation of BNNSs by bipolar nanosecond pulse dielectric barrier discharge at atmospheric pressure with water to increase thermal conductivity and breakdown strength. Yang et al [39] developed resin-impregnated insulation paper (RIP) by adding h-BN nanoflakes into epoxy, which results in increased thermal conductivity up to 0.478 W/m-K (139%) compared to untreated RIP along with improvement in breakdown strength and F I G U R E 4 Thermal conductivity versus content of nano h-BN [39] [Color figure can be viewed at wileyonlinelibrary.com] F I G U R E 5 Scanning electron microscope (SEM) images of 40 wt% boron nitride (BN) filed epoxy composite with different sizes of BN. [40] (A) 1 μm size of BN/epoxy.…”
Section: Thermal and Dielectric Performance Of Bn/epoxy Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Mi et al [38] used the plasma technique to increase hydroxylation of BNNSs by bipolar nanosecond pulse dielectric barrier discharge at atmospheric pressure with water to increase thermal conductivity and breakdown strength. Yang et al [39] developed resin-impregnated insulation paper (RIP) by adding h-BN nanoflakes into epoxy, which results in increased thermal conductivity up to 0.478 W/m-K (139%) compared to untreated RIP along with improvement in breakdown strength and F I G U R E 4 Thermal conductivity versus content of nano h-BN [39] [Color figure can be viewed at wileyonlinelibrary.com] F I G U R E 5 Scanning electron microscope (SEM) images of 40 wt% boron nitride (BN) filed epoxy composite with different sizes of BN. [40] (A) 1 μm size of BN/epoxy.…”
Section: Thermal and Dielectric Performance Of Bn/epoxy Compositesmentioning
confidence: 99%
“…Mi et al [ 38 ] used the plasma technique to increase hydroxylation of BNNSs by bipolar nanosecond pulse dielectric barrier discharge at atmospheric pressure with water to increase thermal conductivity and breakdown strength. Yang et al [ 39 ] developed resin‐impregnated insulation paper (RIP) by adding h‐BN nanoflakes into epoxy, which results in increased thermal conductivity up to 0.478 W/m‐K (139%) compared to untreated RIP along with improvement in breakdown strength and space charge properties using pulsed electro‐acoustic system.…”
Section: Thermal and Dielectric Performance Of Bn/epoxy Compositesmentioning
confidence: 99%
“…Yanget al reported that when h-BN was added to an epoxy resin-impregnated insulation paper, its thermal conductivity increased by 139%. Meanwhile, the breakdown strength remained constant and the inhibition of space charges was observed [13]. Zhanget al investigated the effects of the addition of boron nitride nanospheres into the epoxy resin matrix on the thermal conductivity and insulating performance of composites.…”
Section: Introductionmentioning
confidence: 99%
“…During operation, the ambient temperature of the valve side bushing is high, and its current-carrying central tube carries a large harmonic current component, in addition to the fundamental current. Affected by the harmonic current skin effect, the valve side bushing with insufficient current capacity is prone to insulation failure, which is caused by overheating inside bushing during the highest load period [1][2][3][4][5][6][7][8][9]. In recent years, Yimin, Baoji, Fengjing etc.…”
Section: Introductionmentioning
confidence: 99%